The acceptance of dental operating microscope among advance education specialty programs in endodontics in the middle east - Mansour Alrejaie; Nada M Al-Ibrahim; Khalid Al-Fouzan (Wolters Kluwer Medknow Publications, 2012)
Aim: To present the current situation of dental operating microscopy (DOM) training in the available Advance Specialty Education Programs in Endodontics in Arab Middle-Eastern countries. Materials and Methods: A web-based survey was sent to the electronic mail address of Advance Specialty Education programs of 15 Arab and middle east countries. The questions were limited to those who have an advanced specialty education program in Endodontics at their University if they are using an operating microscope? Results: Out of 15 countries, only 4 countries have microscopic technology in their Advance Education Programs in Endodontics. Conclusion: Few Arab Middle-Eastern countries have DOM in their advance education programs in endodontics. The highest authority in advancing endodontic education in the Arab Middle-East should consider in the near future the importance of this technology as standard care in teaching advance endodontics. An advance workshops should be organized regularly to provide enough knowledge about this standard educational technology.